A new pathway of monomethylmercury photodegradation mediated by singlet oxygen on the interface of sediment soil and water. (May 2019) - Sheng, Feng; Ling, Jingyi; Hong, Ran; Jin, Xin; Wang, Chao; Zhong, Huan; Gu, Xueyuan; Gu, Cheng
Abstract: Photodegradation is an important pathway for monomethylmercury (MeHg) degradation in aquatic ecosystems. In this process, dissolved organic matter (DOM) plays an essential role. However, little information is available regarding the photo-transformation of MeHg in shallow aquatic environments, where a significant portion of MeHg is associated with soil suspensions. In this study, 14 soils sampled from different sites in China were used to simulate these conditions. Our results clearly demonstrated that soil organic matter (SOM) was the most important factor controlling the MeHg photodegradation in suspension. Degradation in this heterogeneous aqueous system was shown to be mediated by the 1 O2 produced by organic matter on the surface of the soil particles rather than by DOM. This was confirmed by the strong correlation between the kinetics rate constant of MeHg degradation and steady state concentrations of 1 O2 ( R 2 = 0.81). Our results propose a new pathway of MeHg induced by sediment soils under sunlight irradiation. Identification of this pathway may improve the estimates of potential ecological risk of Hg in shallow field ecosystems. Graphical abstract: Image 1 Highlights: MeHg can be photo-degraded with simulated sunlight when soil particles are existed in natural shallow. Soil organic matter rather than dissolved organic matter plays a dominant role in MeHg photodegradation. Singlet oxygen is dominating active species for MeHg photodegradation on the surface of soil particles.